Texas Ranger - Patterson, James, 1947-; Bourelle, Andrew (2018)
"Across the ranchlands and cities of his home state, Rory Yates's discipline and law-enforcement skills have carried him far--from local highway patrolman to the honorable rank of Texas Ranger. A tough case in Waco has jeopardized Yates's chances at promotion, and he decides to take time off to recharge with his family in their small-town hometown, Redbud. He arrives and finds a horrifying crime scene--and a scathing accusation: he is named a suspect in the murder of his ex-wife, Anne, a devoted teacher whose only controversial act ever was deciding to end her marriage to a Ranger. In search of the killer, Yates follows the Ranger creed--never to surrender--into the inferno of the most twisted and violent minds he's ever encountered. That code just might bring him out alive."--
Includes excerpt from: Juror #3 / by James Patterson and Nancy Allen.
Keywords: Texas Rangers -- Fiction; Murder -- Investigation -- Fiction; Thrillers (Fiction); Western fiction; Detective and mystery fiction